2019
DOI: 10.3390/ani9070440
|View full text |Cite
|
Sign up to set email alerts
|

Welfare-aligned Sentience: Enhanced Capacities to Experience, Interact, Anticipate, Choose and Survive

Abstract: The focus of this opinion is on the key features of sentience in animals which can experience different states of welfare, encapsulated by the new term ‘welfare-aligned sentience’. This term is intended to exclude potential forms of sentience that do not enable animals in some taxa to have the subjective experiences which underlie different welfare states. As the scientific understanding of key features of sentience has increased markedly during the last 10 to 15 years, a major purpose here is to provide up-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 113 publications
(267 reference statements)
0
57
0
1
Order By: Relevance
“…However, such views are not widely accepted by animal welfare and other scientists [15,20,30]. Instead, the majority hold that animals would consciously experience pain when it can be shown that coincident physiological and behavioural responses are indeed due to nociceptive inputs from areas of the body subject to noxious stimulation [13][14][15]20,21,30]. Such arguments rely on the cautious application of scientifically informed best judgement, which underlies conclusions that recognise a legitimate role for what has come to be known as "critical anthropomorphism" [30,31].…”
Section: Cerebrocortical Involvement In the Conscious Experience Of Pmentioning
confidence: 99%
See 4 more Smart Citations
“…However, such views are not widely accepted by animal welfare and other scientists [15,20,30]. Instead, the majority hold that animals would consciously experience pain when it can be shown that coincident physiological and behavioural responses are indeed due to nociceptive inputs from areas of the body subject to noxious stimulation [13][14][15]20,21,30]. Such arguments rely on the cautious application of scientifically informed best judgement, which underlies conclusions that recognise a legitimate role for what has come to be known as "critical anthropomorphism" [30,31].…”
Section: Cerebrocortical Involvement In the Conscious Experience Of Pmentioning
confidence: 99%
“…Instead, the majority hold that animals would consciously experience pain when it can be shown that coincident physiological and behavioural responses are indeed due to nociceptive inputs from areas of the body subject to noxious stimulation [13][14][15]20,21,30]. Such arguments rely on the cautious application of scientifically informed best judgement, which underlies conclusions that recognise a legitimate role for what has come to be known as "critical anthropomorphism" [30,31]. Moreover, evidence that the cerebral cortex of mammals has an integral role in the conscious experience of pain [32][33][34] further supports this reasoned approach.…”
Section: Cerebrocortical Involvement In the Conscious Experience Of Pmentioning
confidence: 99%
See 3 more Smart Citations